EARNINGS MANAGEMENT: EVALUATION OF AUDIT COMMITTEE ACTIVITY IN INDONESIA - Yulius Kurnia Susanto; Kevin Edrick Yangrico (Politeknik Keuangan Negara STAN, 2020)
The paper is intended to provide evidence of the effect audit committee meeting, attendance meeting, size, appointment, audit quality, managerial ownership, firm size, leverage, profitability, operating cash flow and sales growth on earnings management. The population of the paper are public non financial companies from 2016 to 2018. The paper uses 85 samples selected through purposive sampling method, hence amounting to 255 firm year. The result indicates that audit committee size, managerial ownership, firm size, leverage, profitability, operating cash flow and sales growth statisticall influenced earnings management. Audit committee meeting, attendance meeting, appointment and audit quality have no influence toward earnings management. Audit committee size positively influenced earnings management by ineffeciency while they doing their task to monitor mangement when it is too large. Mangerial ownership positively influenced earnings management because manager have their self interest to get more return from their ownership. Firm size negatively influenced earnings management because larger the firm, more sophisticated control system to monitor management. Leverage positively influenced earnings management by distort financial statement to avoid from debt covenant violation. Profitability positively influenced earnings management by avoiding higher tax charges when company have higher profitability. Operating cash flow negatively influenced earnings management because smaller the entity’s cash inflow will give a bad signal to investor. Lastly, sales growth positively influenced earnings management because of management intention to get bigger bonus.